An Evaluation of the Approaches to Text Modification Used by Lower Secondary CLIL Teachers in Finland - Yu Zi (Universidad de La Sabana, 2022)
This study sets two main objectives to address this research gap in CLIL materials design: to identify and to evaluate teachers' approaches to text modification. The study focuses on four secondary teachers who teach non-language subjects to grades 7-9 in Finland, in English. The qualitative data consist of interviews and teaching materials designed by the participants. A review of over 60 studies is conducted in order to provide a framework for the evaluation of input modification strategies. The studies indicate that elaboration devices seem to enhance L2 comprehension and vocabulary development. The same cannot be as confidently stated about the effect of simplification. This study identifies all three main approaches to text modification in the participants' teaching materials. Regardless of their previous teaching experience, most teachers use elaboration strategies when adjusting the linguistic and cognitive level of texts. More experienced teachers seem to avoid using simplification strategies, whilst less experienced teachers adopt a wide range of strategies. All participants use some types of rediscursification strategy. This study can provide the professionals in the field of CLIL education with an insight into the reality of how CLIL practitioners modify materials. The results may also contribute to CLIL teacher education and in-service training by informing teachers of the commonly used input modification strategies and raising awareness of the effectiveness of these techniques.